2020
DOI: 10.21203/rs.3.rs-30522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial Community Research of Migratory Bird in Chifeng, Neimeng via High-Throughput Sequencing

Abstract: Background: In August 2018, a large number of migratory birds died in Chifeng, Neimeng. We were entrusted by local animal disease prevention and control center to collect the migratory bird epidemic materials and their living environmental water, and in 2019, we collect the local migratory bird stool and their living environmental water again. The bacterial communities in migratory bird epidemic materials, water and aquatic plants are profifiled by high-throughput sequencing of the V3–V4 hypervariable region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Clinical signs were reported from 20 study records and were most often associated with V. cholerae non-O1/O139 [63, 66, 75, 77, 87, 89, 93, 96, 98, 100, 101]. One study reported clinical signs, primarily edema and cellulitis of the gastrointestinal tract, with an experimental inoculation of O1 Ogawa in domestic chickens [87].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical signs were reported from 20 study records and were most often associated with V. cholerae non-O1/O139 [63, 66, 75, 77, 87, 89, 93, 96, 98, 100, 101]. One study reported clinical signs, primarily edema and cellulitis of the gastrointestinal tract, with an experimental inoculation of O1 Ogawa in domestic chickens [87].…”
Section: Resultsmentioning
confidence: 99%
“…as the etiological agents of disease in birds remains only partially answered. Of the 76 studies that surveyed birds for pathogenic Vibrio species, 19 reported disease or death from individuals, scaling up to community level events [63, 66, 75, 77, 87, 89, 93, 96, 98, 100, 101, 108, 115, 118, 121, 125, 127]. Yet, it remains uncertain whether these pathogenic Vibrio species are opportunistic pathogens that contribute to morbidity and/or mortality in already stressed individuals, or whether they can be the primary arbiters of disease [111].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations